Etic Interpreting of Naïve Subjective Personal Introspections of Tourism Behavior: Analyzing Visitors' Stories About Experiencing Mumbai, Seoul, Singapore and Tokyo - Martin, D.; Woodside, Arch; Dehuang, N. (Emerald Group Publishing Ltd., 2007)
Purpose – To demonstrate how brand netnography is useful in showing how visitors interpret the places, people and situations that they experience when traveling. Design/methodology/approach – Through analysis of online consumer stories about their travel experiences, this paper probes how visitors interpret their experiences while visiting cities in Asia. Deconstructing texts written by consumers via Heider's balance theory provides the method of analysis for samples of both positive and negative travel experiences of foreign visitors. Findings – Mapping consumer experiences shows immediate and downstream positive and negative associations of concepts, events, and outcomes in visitors' stories. These maps include descriptions of how visitors live specific destination's unique promises. Research limitations/implications – The population of bloggers who report their experiences may not be representative of the population of all visitors. Practical implications – Blog-journal stories provides the opportunity to collect emic interpretative data unobtrusively. These stories have the potential to influence substantial numbers of future visitors who go online in search of first-person unbiased, unrehearsed reports of others' destination experiences. First-person (emic) reports enable managers of places (brands) to learn and talk in dialects of customers. Originality/value – This paper provides a revisionist proposal to Holt's five-step strategy for building destinations as iconic brands and suggestions for tourism management. The revisionist view includes interpreting consumers' own interpretations of their place experiences.